2021
DOI: 10.1016/j.bios.2021.113329
|View full text |Cite
|
Sign up to set email alerts
|

A portable triboelectric spirometer for wireless pulmonary function monitoring

Abstract: free information in English and Mandarin on the novel coronavirus COVID-19. The COVID-19 resource centre is hosted on Elsevier Connect, the company's public news and information website.Elsevier hereby grants permission to make all its COVID-19-related research that is available on the COVID-19 resource centre -including this research content -immediately available in PubMed Central and other publicly funded repositories, such as the WHO COVID database with rights for unrestricted research re-use and analyses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
63
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 107 publications
(64 citation statements)
references
References 54 publications
1
63
0
Order By: Relevance
“…[7][8][9][10][11][12][13][14][15][16] TENG can convert mechanical motion into electrical signals, allowing it to function as a self-powered sensor. [17][18][19][20] However, the data generated by TENGs present challenges for analysis, including large volume, high noise and poor continuity. Attempts to process TENG data using traditional analysis methods have met with long operation cycles and low efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][11][12][13][14][15][16] TENG can convert mechanical motion into electrical signals, allowing it to function as a self-powered sensor. [17][18][19][20] However, the data generated by TENGs present challenges for analysis, including large volume, high noise and poor continuity. Attempts to process TENG data using traditional analysis methods have met with long operation cycles and low efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…While research is still in its early stages, promising results have been reported. TENG-based wound healing systems hold a collection of compelling features including portable size, [46,137,138] flexibility, [139,140] low cost, making them a promising, emerging biotechnology to advance the field of wound healing. Research efforts need to continue to address several bottlenecks in the field of TENG-based wound healing.…”
Section: Conclusion and Perspectivementioning
confidence: 99%
“…More recently, a third technological wave is coming where patients can take the lab with them through wearable bio-marker monitoring [1][2][3]. Wearable technology can be an innovative solution to current medical problems with the ability to continuously monitor both physiological and biochemical markers and physical activities and behaviors [4][5][6][7][8]. Vital signs such as heart rate, body temperature, and blood pressure are measured [9,10].…”
Section: Introductionmentioning
confidence: 99%